2019
DOI: 10.1186/s13099-019-0282-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular determinants of colistin resistance among commensal Enterobacteriaceae isolated from poultry in northwest of Iran

Abstract: BackgroundThe emergence of colistin-resistant Enterobacteriaceae from human and animal sources is a public health concern as this antibiotic is considered to be the last line therapeutic option for infections caused by multidrug-resistant Gram-negative bacteria. Here we aimed to determine the prevalence of colistin resistance, among enterobacteria isolated from poultry and the possible underlying colistin resistance mechanisms.MethodsA collection of 944 cloacal samples were obtained from poultry and screened f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Similar resistance pattern was screened in China [2]. Another study reported from Iran had showed 77.7% resistance to ciprofloxacin, 33.3% resistance to gentamicin but no resistance to Imipenem [39]. A study from China reported higher rate of resistance to tetracycline (90%), cefixime (71.4%), and ceftazidime (66.1%) in E. coli isolates [33].…”
Section: Discussionsupporting
confidence: 59%
“…Similar resistance pattern was screened in China [2]. Another study reported from Iran had showed 77.7% resistance to ciprofloxacin, 33.3% resistance to gentamicin but no resistance to Imipenem [39]. A study from China reported higher rate of resistance to tetracycline (90%), cefixime (71.4%), and ceftazidime (66.1%) in E. coli isolates [33].…”
Section: Discussionsupporting
confidence: 59%
“…Our study showed that colistin resistance was as high as 43.75%, contrary to known resistance rates to polymyxins, which are generally between 10% and 23% [37,38]. Colistin-resistant organisms had been postulated to spread from animals to human [39,40,41,42], suggesting the concept of one health. Observational studies have shown that polymyxins are used profusely in animal feed in the community to enhance growth.…”
Section: Discussionmentioning
confidence: 57%
“…The mcr-1 gene is primarily found in E. coli and K. pneumoniae of human origin, which is in line with our study. The plasmid-mediated Col-R possibly developed in animals and was ultimately transmitted to humans [5,32,33]. The four human isolates which harboured mcr-1 in our study were isolated from one septic ICU patient and three patients with urinary tract infections from different wards.…”
Section: Discussionmentioning
confidence: 81%